Vulnerable salvation: Evangelical Protestant leaders and institutions, drug use and HIV and AIDS in the urban periphery of Rio de Janeiro - Garcia, Jonathan (2011)
This analysis focuses on the evangelical Protestant responses to drug use and HIV prevention, treatment and care in the urban periphery of Rio de Janeiro. We question how religious institutions, and the positions of pastors, create or reduce various elements of societal illness and vulnerability. We aim to show that the views of pastors may symbolise a form of social regulation that may have a meaningful social impact on drug use and HIV and AIDS. The interviews of 23 evangelical religious leaders were collected using a theoretical sample and analysed through a grounded theory approach. Two case studies of evangelical drug rehabilitation centres are derived from five qualitative interviews. Evangelical drug rehabilitation centres generally reflect pastors' discourses of reintegration into social networks including marriage, family, and employment. We found important differences in the discourses and practices in private versus state-funded rehabilitation centres that may reveal ways social and programmatic vulnerabilities may affect the efficacy of public health interventions.